FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PERAWAT KAMAR BEDAH DALAM PENERAPAN SURGICAL SAFETY CHECKLIST - Nur " Rahmawati; Siti Rahmalia HD; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract This research aimed to identify the factors associated with compliance of operating room nurses in the application of surgical safety checklist (SSC) in the Central  Surgery Installation of  general hospitals Arifin Achmad Pekanbaru. The Design of this research used descriptive correlation with approach cross sectional. The total samples in the research were 42 people respondents was taken based on the criteria of inclusion using a purposive sampling technique. The instrument in this research used a questionnaire for variables of knowledge, attitude, capability and motivation and the observation sheets of surgical safety checklist (SSC) for the variable compliance that have tested the validity and reliability with the results of Cronbach's Alpha knowledge α = 0.876, the attitude of α = 0.888, the capability of α = 0.897, and motivation α = 0.919. The data was analysed by univariate analysis to determine the frequency distribution and bivariat by used chi-square test. The results showed there is no significant relationship between the level of knowledge (p value = 0,995), attitude (p value = 0,734), capability (p value = 1.000) and motivation (p value = 0.562) with compliance in the application of the SSC. The results of this research recommend to hospital institutions to improve the dissemination and monitoring of compliance with operating room nurses in applying SSC to provide safe and quality surgery for patients. Key words: attitude, capability, compliance, knowledge, motivation, surgical safety checklist